Studying the research scope of mathematics education specialists using keywords - Younes Karimi Fardinpour (مجله علم‌سنجی کاسپین, 2018)
Background and aim: Due to the importance of keywords in the field of research and scientometrics, the keywords used in scientific outputs of mathematics education specialists were investigated in this study to determine the scope of their research. Material and methods: This cross-sectional study was conducted on the Persian scientific papers published by mathematics education specialists who were the first author and published at least three papers for a 25-year period from 1993 to 2017. Under these conditions, 48 papers presented by eight mathematics education specialists were identified. Descriptive and inferential statistics were used to process the number and repetition of keywords. Findings: Out of 204 keywords, 10 keywords were applied 44 times repeatedly (or synonymously). The ratio of total articles to duplicate keywords was 66% and the ratio of duplicate keywords to total keywords was 22%. Linear regression test indicated a direct relationship between the number of articles and ratio of duplicate keywords. Conclusion: The high proportion of duplicate keywords suggests the subject similarity and focus of articles of mathematics education specialists in Iran.